2014
DOI: 10.1002/eji.201444904
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB is crucial in proximal T‐cell signaling for calcium influx and NFAT activation

Abstract: In the accepted model of T-cell activation, parallel signal transduction pathways activate the transcription factors NF-κB, NFAT and AP-1 to drive clonal expansion of T cells in response to antigen. Genome-wide transcriptional profiling following antigen-induced CD8+ T-cell activation in C57BL/6 mouse T cells revealed that genes regulated by NFAT were also reduced in the absence of NF-κB p50 and cRel subunits. Importantly, p50−/−cRel−/− CD8+ T cells had significantly diminished NFAT and AP-1 activation compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Consistent with an intermediate expression profile by combination-treated CD8+ T cells, cluster 5 genes included those with both positive (e.g. Rel , Lef1 (42, 43)) and negative (e.g TNFAIP3 , CD274 (1, 44)) influences on effector CD8+ T-cell proliferation and/or function. Genes represented in cluster 6 were diverse in function yet included Mir15b , Rgcc and Ctla4 , all inhibitors of T-cell cytokine production and/or proliferation (45, 46), consistent with their preferential suppression in combination-treated CD8+ T cells.…”
Section: Resultsmentioning
confidence: 81%
“…Consistent with an intermediate expression profile by combination-treated CD8+ T cells, cluster 5 genes included those with both positive (e.g. Rel , Lef1 (42, 43)) and negative (e.g TNFAIP3 , CD274 (1, 44)) influences on effector CD8+ T-cell proliferation and/or function. Genes represented in cluster 6 were diverse in function yet included Mir15b , Rgcc and Ctla4 , all inhibitors of T-cell cytokine production and/or proliferation (45, 46), consistent with their preferential suppression in combination-treated CD8+ T cells.…”
Section: Resultsmentioning
confidence: 81%
“…Activation of Lck (pLck Tyr394) is central to the initiation of TCR signaling pathways 35 . Activated Lck phosphorylates ZAP-70 that, in turn, activates the transcription factors NFAT and AP-1, thereby driving T-cell immune response to antigen 36 . Interestingly, we observed that wild type Lnc-Tim3 reduced the activation of transfactor NFAT1 and AP-1.…”
Section: Discussionmentioning
confidence: 99%
“…The NFAT and NF-κB signaling pathways synergistically activate T cells ( 20 ). NF-κB is a transcription factor that regulates the expression of inflammatory cytokines and genes essential for the proliferation and survival of T cells ( 21 ).…”
Section: Discussionmentioning
confidence: 99%